Measurement of Foramen Magnum Dimensions in Computed Tomography of Head - Paudel, Sharma; Yadav, Dorik Lal; Kayastha, Prakash; Suwal, Sundar; Dahal, Prajwal; Maharjan, Santosh; Regmi, Pradeep Raj (Nepal Journal of Medical Sciences, 2023)
Introduction: Dimensions of the foramen magnum are clinically important because of the vital structures passing through it and for sex determination of the skull. The objective of this study was to measure various dimensions of the foramen magnum in Computed Tomography (CT) and correlate them with sex. Methods: Descriptive cross-sectional study was done on 120 CT head images in the Department of Radiology and Imaging, from July to October 2019. The shape of the foramen magnum (FM), anteroposterior diameter (APD), transverse diameter (TD), FM area and FM index were calculated. Statistical analysis was done with SPSS 25 and Excel 2016. Discriminant function analysis and binary logistic regression analysis were used for gender verification. RESULTS: The mean values of the APD, TD, area and FM index in males and females were 33.56 ± 4.30 mm, 29.76 ± 4.10 mm, 792.94 ± 191.60 mm2, 85.01 ± 8.67 and 30.01 ± 2.04 mm, 25.33 ± 4.6 mm, 599.63± 128.13 mm2, 83.17 ± 7.78 respectively. All dimensions were significantly greater in males (r = 0.906, P<0.001). The most common shape of the foramen magnum was oval (40.8%). The accuracy of sex identification was 68.3% using dimensions of the foramen magnum. Conclusion: There was sexual dimorphism in the diameter and area of the foramen magnum which can be used for sex determination.